Is problem based learning a better teaching tool as compared to didactic lectures for the undergraduate students? - Joshi, Hari Shankar; Katyal, Rashmi; Singh, Arun; Joshi, Gaurav; Chandra, Shalini; Singh, Kashmir (International Journal Of Community Medicine And Public Health, 2017)
Background: PBL is an educational approach in which complex problems serve as the context and the stimulus for learning. In PBL classes, students work in teams to solve one or more complex and compelling "real world" problems. They develop skills in collecting, evaluating, and synthesizing resources as they first define and then propose a solution to a multi‑faceted problem. The objectives of the study were to acknowledge the students about problem based learning; to assess the effectiveness and outcome of the teaching methodologies i.e. didactic lectures versus PBL; recommendation of incorporation of PBL or traditional teaching method as a teaching tool. Methods: Medical undergraduate (UG) students admitted in RMCH, Bareilly, India. A total of 112 students divided into three batches (36, 33 and 33 students) participated in a systematically conducted PBL session in community Medicine department during the middle of their academic year after having experienced at least 4 months of traditional teaching in community medicine. Perception of the faculty was also taken on Likert’s scale. Responses to the items in the questionnaire was scored as follows: traditional much better (1), traditional better (2), both the same (3) PBL better (4), or PBL much better (5). Appropriate Statistical analysis using appropriate tests will be done. Results: Information gathering and student-teacher relationship is more through traditional method of teaching as compared to PBL which is more in favour of development of interest, motivation, learning efficiency, curiosity, questioning attitude, interpersonal relationship, independent thinking and reasoning.. Conclusions: It can be very well included that introduction of PBL as the teaching modality among the students can improve the quality of medical education as per the evaluation done through the introduction of Likert’scale.